2006
DOI: 10.1111/j.1365-2206.2006.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental substance misuse and child care social work: findings from the first stage of a study of 100 families

Abstract: Parental misuse of drugs or alcohol is known to be a common issue for child care social workers, yet there has been surprisingly little British research on the topic. The study reported here attempts to address this gap. All files going for long‐term allocation in four London boroughs over on average 1 year were examined (290 files). Parental substance misuse (PSM) emerged as a major feature of social work caseloads. Of the 290 cases, 100 (34%) involved concerns about parental substance misuse. The families in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 5 publications
2
58
0
2
Order By: Relevance
“…Forrester and Harwin (2006)'s recent study in four London Boroughs of newly-allocated social work cases found a similar proportion of substance use across the authorities, between 30 and 41%. Alcohol use was slightly more prevalent than drug use.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Forrester and Harwin (2006)'s recent study in four London Boroughs of newly-allocated social work cases found a similar proportion of substance use across the authorities, between 30 and 41%. Alcohol use was slightly more prevalent than drug use.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Alcohol-related harm has a significant impact on the day-today work of social workers and is associated with adverse outcomes for the diverse range of people they are in contact with (see Anderson, Chisholm, & Fuhr, 2009;Dance, Galvani, & Hutchinson, 2014;Forrester & Harwin, 2006). The UK National Drug and Alcohol Strategy (H. M. Government, 2010) acknowledged the key role of social work and social care (the provision of personal care, protection or social support services to people with needs arising from illness, disability, ageing or poverty) in addressing problematic alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…Le risque accru de placement pour ces enfants est aussi bien documenté par la recherche. Les études comparatives indiquent clairement que les enfants nés dans un contexte de consommation maternelle sont plus susceptibles d'être retirés de leur milieu familial que les autres enfants dont la mère ne présente pas ce type de problème 13,14 . La crainte de se voir retirer la garde de l'enfant et la stigmatisation dont les femmes consommatrices sont l'objet nuisent à une intervention de qualité visant à prévenir les risques prénatals 1 .…”
unclassified